2001
DOI: 10.1002/1097-0215(20010601)92:5<718::aid-ijc1257>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical evaluation of a methotrexate-albumin conjugate (MTX-HSA) in human tumor xenograftsin vivo

Abstract: Methotrexate covalently bound to human serum albumin in a 1:1 molar ratio (MTX‐HSA) is a new macromolecular drug which is currently being studied in phase I clinical trials by the German Association for Medical Oncology (AIO) Phase I/II study group. Previous studies have shown that MTX‐HSA differs favorably from unbound MTX in terms of plasma half‐life time, tumor accumulation of albumin and uptake mechanisms into cancer cells. To achieve optimal drug efficacy, repeated treatment cycles were necessary. To eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 27 publications
0
40
0
1
Order By: Relevance
“…Like many clinical cancers, they are resistant to native methotrexate due to transport deficiencies caused by an epigenetic alteration that down-regulates the expression of the reduced folate carrier (22,23). Hence, in this study, MDA-MB-231 cells were treated with methotrexate bound to albumin (17,24,25), which enters the cells by albuminmediated endocytosis (25) and circumvents the methotrexate transport deficiency of MDA-MB-231 cells. The other cell lines were treated with free methotrexate.…”
Section: Resultsmentioning
confidence: 99%
“…Like many clinical cancers, they are resistant to native methotrexate due to transport deficiencies caused by an epigenetic alteration that down-regulates the expression of the reduced folate carrier (22,23). Hence, in this study, MDA-MB-231 cells were treated with methotrexate bound to albumin (17,24,25), which enters the cells by albuminmediated endocytosis (25) and circumvents the methotrexate transport deficiency of MDA-MB-231 cells. The other cell lines were treated with free methotrexate.…”
Section: Resultsmentioning
confidence: 99%
“…Based on an observation that tumors catabolize excessive quantities of albumin (14,15), several attempts to use albumin as a carrier for chemotherapeutic agents have been reported (16)(17)(18). In addition, Abraxane, which uses albumin to formulate and solubilize Taxol, is reported to have better biodistribution properties and reduced toxicity relative to other Taxol formulations (42).…”
Section: Discussionmentioning
confidence: 99%
“…Known to accumulate in and be catabolized by tumors, albumin has previously been pursued as a delivery vehicle for chemotherapy (14)(15)(16)(17)(18). Combining this observation with immunotherapy, we explore the ability of an albumin-binding Fab (AB.Fab) to specifically target tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Using the coupling procedure developed in our laboratory and exerting a 1:1 molar loading ratio, the distribution pattern of the conjugate in vivo is identical with underivated albumin, demonstrating that the native character of the protein is not affected (21,22). Preclinical studies have shown antitumor activity of MTX-HSA in rat tumor models (23,24) and in a variety of human xenograft tumors in nude mice (25). Furthermore, MTX-HSA has shown promising results on the tumor growth, a plasma half-life equivalent to that of HSA, and no immogenicity, and it was well tolerated in a clinical phase I trial for cancer treatment (26).…”
mentioning
confidence: 88%